Implementasi Kebijakan Penatausahaan Aset Daerah di Kabupaten MAPPI - Benediktus Yoseph Engelbertus Rumlus; Muhammad Sawir; Iqbal Miftakhul Mujtahid (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This study aims to determine The results of this study indicate that from the aspect of communication, regional asset management reflects the communication network outside the organization, namely in the organization of regional asset management and users of regional assets. Resource aspects. Resources include comprehension and understanding of administration are still very minimally related to the implementation of the elimination of unproductive regional assets, this can result in failures that occur in the Mappir Regency Government, thus inhibiting the regional autonomy of the Mappir Regency Government because unproductive assets do does not provide benefits for the Mappir Regency Government but drains maintenance costs. Distribution aspects. The attitude of the administration has not reflected the marginal commitment related to the implementation of SOP in the implementation of assertive and unproductive administration. Bureaucratic Structure Aspect. The bureaucratic structure of the administration does not have overlapping authority because the organization is led by one leader, so that only one leader directs and the decisions made are clear. In addition, the organizational structure has been in accordance with the division of labor and the objectives of the organization, the division of labor is to prevent shifts between members of the organization and work can be done with mutual cooperation with the respective divisions. The function of the division of labor is also to facilitate the work of each division and can be evaluated regarding the tasks and responsibilities of the division of labor will also reduce complexity because there is a grouping of work. In addition, the division of labor will also be able to measure how much is doing what and how the results are achieved. Keywords; asset management, policy implementation